The Influence of Provincial Minimum Wage, Human Development Index, Illiteracy Rate, and Unemployment Rate on Poverty - Khairunnisa, Syifa; Maknun, Haiatul; Dimas, Vikry (Journal of Islamic Economic Scholar, 2023)
This research aims to examine the influence of Provincial Minimum Wage (UMP), Human Development Index (HDI), Literacy Rate (AMH), and the unemployment rate on the poverty level in Java Island. The observation in this study was conducted using data from 2018 to 2020 accessed through the Central Statistics Agency. Multiple linear regression analysis was chosen as the data analysis technique in this research, and the SPSS software supported the data analysis steps. The results of this study indicate that the Provincial Minimum Wage, Human Development Index, and unemployment rate have a significant influence on the poverty level of Java Island. However, the Literacy Rate shows results that tend to have no significant impact